Effect of the Incorporation of Biomass in the Carbonization of Waste Electrical and Electronic Equipment - Roberta Mota-Panizio; Luis F. Carmo-Calado; Octávio Alves; Catarina Nobre; J. L. Silveira; Paulo Sérgio Duque de Brito; Margarida Gonçalves (Proceedings, 2021)
The behavior of chars from the carbonization process were studied when the lignocellulosic biomass was incorporated into the waste of electrical and electronic equipment for chlorine removal. Tests were performed at 300°C with a heating rate of 15°C/min and residence time of 60 min. Compositions studied had 100, 75, 50, 25 and 0% of waste electrical and electronic equipment (WEEE) in the mixtures. The composition of 50% WEEE with 50% lignocellulosic biomass presented the best char properties, having an increment of the calorific value in 5.5% relative to the initial value, and chlorine removal of 23.4% when compared to the forestry biomass.